PENGARUH HARGA, PROMOSI DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PRODUK UMKM DI CAR FREE DAY SITUBONDO - Arya Lenza Lambang; Ahmad Hafas Rasyidi; Sri Ayudha Mujiyanti (MANAJEMEN, 2025)
The increasingly intense and competitive competition among companies in the business world has encouraged business actors to continuously strive to increase sales volume in order to maximize a company's sales profits. This study used multiple regression analysis and SPSS 23 software. The results of this study indicate that Price (X1) obtained a significant probability value of 0.003 from the SPSS test. Since the significance probability is less than 0.05, it can be concluded that price has a negative and significant effect on sales volume. Promotion (X2) obtained a significant probability value of 0.00 from the SPSS test. Since the significance probability is less than 0.05, it can be concluded that promotion has a positive and significant effect on sales volume. Distribution Channel (X3) The results of the test with SPSS obtained a significant probability value of 0.010. Since the significance probability is less than 0.05, it can be concluded that the distribution channel has a positive and significant effect on sales volume. Based on Table 5, the results of the coefficient of determination test obtained an Adjusted R Square value of 0.270, meaning that 27% of MSME sales volume in CFD is influenced by the variables of price, promotion, and distribution channel, while the remaining 73% is influenced by other variables. Based on Table 5, the results of the coefficient of determination test show that the Adjusted R Square value obtained is 0.270, which means that 27% of MSME sales volume in CFD is influenced by the variables of price, promotion, and distribution channel, while the remaining 73% is influenced by other variables.